The amplitudes and phases of tidal constituents from Harmonic Analysis at two stations in the Gaspar Strait of Bangka Belitung - Yuliardi, Amir Yarkhasy; Heltria, Septy; Taj, Kemal; Natih, Nyoman M N (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
The waters of the Bangka Belitung islands are shallow waters that are affected by tides. The tides in these waters originate from the propagation of the Natuna and Java Seas, so they have unique characteristics. This study aims to analyze the amplitude and phase difference at 2 stations representing Bangka and Belitung Islands with the final output of LAT and HAT information as marine cadastral recommendations at Tanjung Pesona and Tanjung Tinggi stations and safe depths for ports in PPN Sungailiat and PPN Tanjung Pandan. . Tidal data for 1 year with time intervals of 1 hour in 2015 were used to extract the harmonic components to determine the type of tide and calculate the tidal level at each station. The results obtained are 19 harmonic components with a diurnal tide type. The water level at Tanjung Pesona is higher than the high Tanjung, which is described by tidal levels with HAT 2.64 and 1.72 m. Safe depth of harbor pond. In the LAT condition (lowest recess), the water level at Tanjung Pesona station is above the Sungailiat PPN pool's maximum depth; on the other hand, the Tanjung Pandan PPN LAT is 0.44 m below the maximum depth of the port pool.Key Word: Bangka Belitung, chart datum, LAT, HAT, tidal level